1992
DOI: 10.1002/mrm.1910250107
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent quantification of tissue metabolism and blood flow via 2h/31P NMR in Viva iii. alterations of muscle blood flow and metabolism during sepsis

Abstract: In the conclusion of this series of reports, the application of 31P/2H NMR to investigate the pathophysiology of sepsis in rat hindlimb muscle is demonstrated. Sepsis decreased muscle [PCr] by 18%, 18 +/- 4 SD vs 22 +/- 4 SD mmol/kg tissue wet wt (P = 0.01) in control rats but [ATP] was unchanged, 6 mmol/kg tissue wet wt (P = 0.2). The derived free cytosolic [ADP] in the two groups was similar, [ADP]septic = 0.023 +/- 0.004 SD and [ADP]control = 0.021 +/- 0.003 SD mmol/kg tissue wet wt, and not statistically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The rate of tissue uptake of D,O following intravenous bolus injection is widely used to measure perfusion rate (in milliliters/100 g of tissue x minutes) because it is approximately fully extracted ( E = 1.0) from the capillary bed during a single passage (i.e., during the mean transit time). A large body of work (e.g., [11][12][13][14] validates the use of magnetic resonance detection of D,O uptake for accurate perfusion measurements. Kim and Ackerman et 01. measured perfusion rates in rodent kidney, liver, brain, muscle and tumor (11.…”
Section: Introductionmentioning
confidence: 98%
“…The rate of tissue uptake of D,O following intravenous bolus injection is widely used to measure perfusion rate (in milliliters/100 g of tissue x minutes) because it is approximately fully extracted ( E = 1.0) from the capillary bed during a single passage (i.e., during the mean transit time). A large body of work (e.g., [11][12][13][14] validates the use of magnetic resonance detection of D,O uptake for accurate perfusion measurements. Kim and Ackerman et 01. measured perfusion rates in rodent kidney, liver, brain, muscle and tumor (11.…”
Section: Introductionmentioning
confidence: 98%
“…The relationship between intracellular sodium accumulation and high-energy phosphate depletion was demonstrated during rat leg ischemia by 23 Na/ 31 P spectroscopy (7). The possibility of concurrent quantification of tissue metabolism and blood flow via 2 H/ 31 P NMR was shown and validated in the rat and was applied to investigate an experimental model of sepsis (8). Surprisingly, and rather disappointingly, this did not develop into a plethora of applications.…”
mentioning
confidence: 99%
“…From the 1980s until the present, applications of flow NMR have rapidly spread, including the biological sciences. For example, in vivo 31 P flow NMR studies 14 of ATP metabolites in blood have been reported. Similar recycled-flow NMR experiments with other high-sensitivity nuclei (e.g., 2 H, 19 F, etc.)…”
mentioning
confidence: 99%